The inclusion of people with hepatitis C within disability studies. Issue 1 (2nd January 2017) - Mack, Heather; Paylor, Ian
ABSTRACT: This article adopts a critical position regarding the 'illness is not disability' debate by framing hepatitis C both as a lived, physical impairment and a socio-cultural disability/illness. This article draws on qualitative in-depth interviews with 21 people who live(d) with hepatitis C in the UK and examines the financial impact of living with hepatitis C and the process of applying and being found eligible for welfare benefits. This article contributes to the discussion around the inclusion of people with HCV within disability studies and argued that there should be greater recognition of the disabling processes and barriers they face in accessing information, support, recognition and treatment. At present, the institutional processes used to define the ability to work and determine eligibility for benefits frequently exclude and marginalize the experience of people with hepatitis C.